Some remarks on time in the analysis of economic events - Biernacki, Marek (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2016)
The paper presents the approaches to time in the theory of economics, and some problems resulting from the manner in which a time variable is used when describing and predicting economic events
Mathematical Economics, 2016, Nr 12 (19), s. 5-14
Keywords: time; economic processes